EXCELLENT CUSTOMER SERVICE DALAM BIDANG PERBANKAN - Farouk, Umar (Politeknik Negeri Semarang, 2017)
Issues on Excellent Customer Service (ECS) have been being much discussed in manymarketing seminars and writings after the rise of public relations or services and the fall ofadvertising is a real phenomenon. In banking institutions ECS, which is then more recognizedas Customer Service in Delivery (CSID), has its crucial roles or functions to improve clients’satisfaction and maintain their loyalty. Banking institutions need professional human resourcesto make it possible to implement programs of ECS effectively. Therefore, giving trainings ofECS for the whole employees is not a choice but an obligatory. Briefly discussed subject mattescover definition of ECS, categories of Customer Service, functions and tasks of Customer ServiceOfficers (CSO’s,), tips of implementing effective interpersonal communication